Adenosine Triphosphate in Health and Disease - Mozsik, Gyula (Physiology, 2019)
This book covers a very important research field; specifically, it tries to decrease the gap between theoretical and clinical research. The tendency of world research is to gain a detailed insight into the living organs of animals and humans. However, we must not lose sight of the problems that these organs can present; for example, we need to understand their molecular and biochemical mechanisms, as well as new drug productions to counteract diseases. Very deep mechanisms can offer new therapeutic pathways in hematology and oncology, among other fields. However, at least 8-l0 years of further clinical studies are necessary to make a final decision regarding the real clinical importance of basic research. Ideally, an interdisciplinary efforts among basic and clinical researchers are necessary in common research fields. At the same time, genetic research is increasing dramatically (e.g. enzyme mutations). The primary aim of this book is to demonstrate how such research can be used in both fields. This book gathers knowledge from experts in basic and clinical science, biochemistry, pharmacology, molecular pharmacology, genetics, and other fields.